FORMULATION AND IN VITRO EVALUATION OF RITONAVIR FLOATING TABLETS BY MELT GRANULATION TECHNIQUE - Velivela, Swapna; Abbulu, Kondae; M., Vinyas; Pati, Nikunja B. (International Journal of Applied Pharmaceutics, 2016)
Objective: The purpose of this study was to formulate Ritonavir floating matrix tablets by melt granulation technique in order to prolong its gastric residence time thereby increasing its bioavailability. Methods: The Ritonavir tablets were prepared by melt granulation technique, using carriers such as Gelucire 43/01, Gelucire 50/02 and Geleol pellets alone or in combinations. Ethyl cellulose was used as drug release rate retarding agent and sodium bicarbonate was used as gas generating agent. The prepared granules were subjected to pre and post compressional parameters. The formulations were optimized on the basis of matrix integrity, duration of floating, swelling behavior and In vitro drug release. Results: The drug-excipients compatibility studies were performed by FT-IR and the study revealed that there is no drug excipients interaction. A combined matrix system containing Gelucire 43/01: Gelucire 50/02 with 1:1 concentration along with HPMC K 15 M shows good drug release pattern with less floating lag time and increased floating duration. Conclusion: The in vitro drug release pattern of Ritonavir floating tablets was fitted to different kinetic models which showed the highest regression for Zero order kinetics with Higuchi mechanism. Keywords: Gelucire 43/01, Gelucire 50/02, Geleol pellets, Swelling behavior